2022
DOI: 10.1093/jxb/erac359
|View full text |Cite
|
Sign up to set email alerts
|

Haploid induction by nanobody-targeted ubiquitin-proteasome-based degradation of EYFP-tagged CENH3 in Arabidopsis thaliana

Abstract: The generation of haploid plants accelerates the crop breeding process. One of the haploidization strategies is based on the genetic manipulation of endogenous CENH3. To extend the haploidization toolbox, we tested whether targeted in vivo degradation of CENH3 protein can be harnessed to generate haploids in Arabidopsis thaliana. We show that a recombinant anti-GFP nanobody fused to either heterologous F-box (NSlmb) or SPOP/BTB ligase (SPOP) proteins can recognize maternally derived EYFP-tagged CENH3 in planta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…To assess the effect of temperature on centromeres, we analyzed the CENH3 signal on pachytene chromosomes in anthers of the Arabidopsis eYFP:CENH3 reporter line (Le Goff et al, 2020; Demidov et al, 2022) grown at 21, 26 and 30°C. While eYFP:CENH3 was readily detectable on pachytene chromosomes at 21°C, the signal decreased significantly at 26°C and declined further at 30°C (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To assess the effect of temperature on centromeres, we analyzed the CENH3 signal on pachytene chromosomes in anthers of the Arabidopsis eYFP:CENH3 reporter line (Le Goff et al, 2020; Demidov et al, 2022) grown at 21, 26 and 30°C. While eYFP:CENH3 was readily detectable on pachytene chromosomes at 21°C, the signal decreased significantly at 26°C and declined further at 30°C (Figure 3A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Plant material and growth conditions Arabidopsis thaliana ecotype Columbia (Col-0), cenh3-4 (Capitao et al, 2021) and spo11-2-3 (Hartung et al, 2007) were generated by crossing HTA10:RFP (Valuchova et al, 2020) and pRPS5A::TagRFP:TUB4 (Prusicki et al, 2019) reporter lines with cenh3-4 mutant and BMF3::BMF3:GFP reporter line, respectively. eYFP:CENH3 reporter line was described and characterized in previous studies (Le Goff et al, 2020;Demidov et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to haploids, diploids, and aneuploids are produced as a result of the recruitment of some chromosomes into the main nucleus and the degradation of other chromosomes (Tan et al, 2015). Recent studies showed that direct degradation of CENH3 via a nanobody-based method produced haploids even though the prior study showed that RNAi-mediated suppression of CENH3 expression did not produce any haploids (Demidov et al, 2022) (Figure 2C).…”
Section: Haploid Breeding: One Inducer Serves All Cultivarsmentioning
confidence: 96%
“…In addition to genetic modification, a parental genome has been eliminated using targeted in vivo degradation of the CENH3 protein. Arabidopsis thaliana haploids were produced by using degraded Green Fluorescent Protein (deGradFP) (Demidov et al ., 2022), a system that uses the ubiquitin‐proteasome pathway in conjunction with a green fluorescent protein (GFP)‐specific nanobody (VHHGFP4) fused to an E3 ligase (Caussinus & Affolter, 2016).…”
Section: Engineering Of Centromeres To Generate Haploid Inducersmentioning
confidence: 99%